2012
DOI: 10.1590/s1516-35982012000500013
|View full text |Cite
|
Sign up to set email alerts
|

Heteroskedasticity for weaning weight of Charolais-Zebu crossbred calves

Abstract: -The objective of the present study was to analyze models with genetic and/or residual heteroskedasticity for genetic evaluation of the weaning weight of Charolais-Zebu crossbred calves. Weaning weight data from 56,965 crossbred calves were analyzed using animal models with different combinations of genetic and residual heteroskedasticity and/or homoskedasticity. The inference on a posteriori distributions of genetic parameters were by the Monte Carlo method via Markov chains. The model with genetic and residu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…This result shows the superiority of the Angus breed, which stands out for having a greater precocity of growth and termination than Zebu. This may be related to the history of selection of the Angus breed, which is known and selected for precocity of growth, whereas the Nelore breed has only been recently selected for growth (Toral et al, 2012), not having been subjected to systematic selection processes in its location of origin.…”
Section: Resultsmentioning
confidence: 99%
“…This result shows the superiority of the Angus breed, which stands out for having a greater precocity of growth and termination than Zebu. This may be related to the history of selection of the Angus breed, which is known and selected for precocity of growth, whereas the Nelore breed has only been recently selected for growth (Toral et al, 2012), not having been subjected to systematic selection processes in its location of origin.…”
Section: Resultsmentioning
confidence: 99%
“…Other works on multiple trait evaluations, carried out with data on beef (Cardoso & Tempelman, 2004;Toral et al, 2012;Lukaszewicz et al, 2015) and dairy (Heins et al, 2011;VanRaden et al, 2011) cattle, showed that variances and heritabilities are specific to each genetic group. Similar results were obtained in the present study, since the additive genetic variances and heritabilities of AFC and 305MY were higher in the 1/2HG groups than in the 5/8HG and 3/4HG groups (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…The lowest averages a posteriori were observed in groups 5/8HG and 3/4HG. These differences may be a consequence of the different processes and intensities of selection to which the different genetic groups were subjected to (Toral et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Feeding systems and specific management for each breed group may be used to improve productivity in multiple-breed cattle production. This can result in heterogeneity of residual variance (Toral et al, 2012). In fact, models with heterogeneous residual variances presented a better fit when compared with the ones with homogeneous residual variances for the genetic evaluation of postweaning weight gain of Nellore-Hereford crosses (Cardoso et al, 2005).…”
Section: Field Datamentioning
confidence: 98%
“…The heterogeneity of variances and covariances among purebred and crossbred cows could occur in multiple breed populations (VanRaden et al, 2007) due to the use of different selection intensities and specific selection processes in groups with different genetic composition (Toral et al, 2012). Therefore, the development and implementation of genetic evaluations that account for genotypic means, genetic covariances among relatives (Lo et al, 1993), and the existence of specific genetic variances for each different breed group (Lukaszewicz et al, 2015) can contribute to the genetic improvement of multiple-breed populations.…”
Section: Introductionmentioning
confidence: 99%